Empirical efficiency measurement in higher education: An overview - Vanesa Valeria D'Elía; Gustavo Ferro (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2019)
This paper reviews the most recent empirical literature that assesses efficiency in higher education. We analyze 76 studies ranging from 1997 to 2018 and classify them according to the methodologies applied and to the definitions used to describe the outputs, inputs, quality and the context variables. We find that 72 percent of the empirical studies use non-parametric approaches. The most recent studies use panel data. The degrees completed are the most frequently used output variable, and only 9 papers include quality variables. Moreover, while only few parametric papers take observed heterogeneity into account, more than 40 percent include environmental variables to address for observed heterogeneity. This review is useful for researchers interested in measuring efficiency, for policy makers and for other educational stakeholders.
Keywords: I23; C13; C14; 330; Higher Education Efficiency; Efficiency Frontier Methods; Stochastic Frontier Analysis; Data Envelopment Analysis